2013
DOI: 10.5194/hess-17-5185-2013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil, land use and climatic factors on the hydraulic conductivity of soil

Abstract: Due to inadequate data support, existing algorithms used to estimate soil hydraulic conductivity, K, in (eco)hydrological models ignore the effects of key site factors such as land use and climate and underplay the significant effects of soil structure on water flow at and near saturation. These limitations may introduce serious bias and error into predictions of terrestrial water balances and soil moisture status, and thus plant growth and rates of biogeochemical processes. To resolve these issues, we collate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(167 citation statements)
references
References 52 publications
9
108
5
Order By: Relevance
“…Although these studies contributed to a better understanding of the effect of alpine ecosystem variations on soil hydraulic properties, they primarily addressed the change patterns of hydraulic properties. Moreover, it has been confirmed that soil physical and chemical properties, such as soil porosity, texture and organic matter content, are closely connected with soil hydraulic properties (Fu et al, 2015;Jarvis et al, 2013;Strudley et al, 2008). However, studies about the quantitative relationships between soil hydraulic properties and physicochemical properties are still relatively limited.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these studies contributed to a better understanding of the effect of alpine ecosystem variations on soil hydraulic properties, they primarily addressed the change patterns of hydraulic properties. Moreover, it has been confirmed that soil physical and chemical properties, such as soil porosity, texture and organic matter content, are closely connected with soil hydraulic properties (Fu et al, 2015;Jarvis et al, 2013;Strudley et al, 2008). However, studies about the quantitative relationships between soil hydraulic properties and physicochemical properties are still relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the inconsistent changing pattern, K s only positively correlated with NCP (Table 3). In fact, arguments about the impact of soil properties on K s and its changes are still under debate (Fu et al, 2015;Jarvis et al, 2013). Hence, further investigations about variations of K s are needed.…”
Section: Influencing Factors Of Alpine Swamp Meadow Degradation On Somentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, pedotransfer functions are widely developed (Cosby et al, 1984;Rawls and Brakensiek, 1989;Wosten et al, 2001;Schaap et al, 2001) and allow describing of the parameters necessary for the resolution of the Richards equation using soil characteristics such as the soil texture and bulk density. Chanzy et al (2008) demonstrated that pedotransfer functions may allow for a good approximation for agricultural soil water representation even though the adequacy of pedotransfer functions close to the surface is still under discussion (Jarvis et al, 2013), especially for wet conditions when preferential flow occurs.…”
Section: -J Tinet Et Al: Development and Evaluation In Bare Soil Comentioning
confidence: 99%
“…CC BY 4.0 License. Estringana et al, 2013) and has a crucial influence on soil hydraulic properties, in particular soil hydraulic conductivity (Gonzales-Soza et al, 2010;Jarvis et al, 2013). Moreover, it is easy to assess in the field or from remote sensing data.…”
Section: Introductionmentioning
confidence: 99%